Construction and Demolition Waste and the Contradictions of Sustainability - Marques, Maurício Dias; Benini, Sandra Medina (National Journal of City Management, 2026)
Objective – This article aims to develop a critical reflection on construction and demolition waste, analyzing it as an expression of the contradictions between the discourse of sustainability and the productive practices that structure the production of urban space. Methodology – This is a theoretical-conceptual study, based on a critical review of specialized literature and normative documents on sustainability, construction, solid waste, and environmental education, without the use of primary empirical data. Originality/Relevance – The originality of the study lies in addressing construction and demolition waste as a central category for understanding the limits of urban sustainability, going beyond approaches restricted to technical management or regulatory compliance. Results – The results indicate that the persistence of waste generation stems from structural choices made throughout the construction industry’s production chain, highlighting the gap between legal advances and effective transformations in construction practices. Theoretical/Methodological Contributions – The study contributes by articulating sustainability, normativity, life cycle, and environmental education, reaffirming the potential of theoretical-conceptual essays for the critical analysis of complex urban processes. Social and Environmental Contributions – From a social and environmental perspective, the article shows that construction and demolition waste intensifies territorial inequalities and environmental impacts, pointing to environmental education as a structuring element for changing productive and cultural practices.